Safety and use of tetanus-diphtheria-acellular pertussis-5 (Tdap5) vaccine during pregnancy: findings from 11 years of reporting to a pregnancy registry. Issue 12 (2nd December 2021) - Switzer, Charlotte; Tikhonov, Ilia; Khromava, Alena; Pool, Vitali; Lévesque, Linda E.
ABSTRACT: The "Adacel (Tdap5) Pregnancy Registry" was used to identify 1182 women who received the tetanus, diphtheria, acellular pertussis [5 components] (Tdap5) vaccine during pregnancy from 2005 to 2016. To evaluate the safety and use of prenatal Tdap5, we calculated the rate of maternal, obstetrical, pregnancy and neonatal outcomes following Tdap5 pregnancy exposure and assessed vaccine uptake by year and trimester of exposure. The most commonly reported maternal adverse events included injection site reactions (2.6%; 95% Confidence Interval 1.8%, 3.7%), nervous system events (1.3%; 0.8%, 2.1%) and musculoskeletal events (1.1%; 0.6%, 1.9%). The most commonly reported complications of pregnancy were hypertension/preeclampsia (5.5%; 3.3%, 8.9%) and gestational diabetes (2.5%; 1.1%, 5.3%), while those for labor and delivery were premature labor (2.9%; 1.4%, 5.7%) and premature membrane rupture (1.5%; 0.4%, 3.8%). These rates were similar to, or lower than those reported for the general population of pregnant women. Among pregnancies with known birth outcomes (N = 275), 90.4% (86.2%, 93.4%) resulted in a live birth, 5.9% (3.6%, 9.5%) in spontaneous abortion, 3.0% (1.4%, 5.8%) in stillbirth, and 0.7% (0.0%, 2.8%) in ectopic pregnancies. Most newborns had normal APGAR scores and birth weights (98.1% and 93.0%, respectively), and only two reported a congenital anomaly (0.7%; 0.0%, 2.8%). An influx of reports in 2012 with third trimester Tdap5 exposure coincided with the 2012 updated Advisory Committee on Immunization Practices recommendations. This analysis did not identify any safety concerns across the continuum of maternal, obstetrical, pregnancy, and neonatal outcomes in women who received Tdap5 vaccination during pregnancy.